Acquisition and amplification of a testis-expressed autosomal gene, SSL, by the Drosophila Y chromosome - Kalmykova, Alla I. (The National Academy of Sciences of the USA, 1997)
The acquisition of autosomal fertility genes has been proposed to be an important process in human Y chromosome evolution. For example, the Y-linked fertility factor DAZ (Deleted in Azoospermia) appears to have arisen after the transposition and tandem amplification of the autosomal DAZH gene. The Drosophila melanogaster Y chromosome contains tandemly repeated Su(Ste) units that are thought to affect male fertility as suppressors of the homologous X-linked Stellate repeats. Here we report the detection of a testis-expressed autosomal gene, SSL [Su(Ste)-like], that appears to be an ancestor of the Y-linked Su(Ste) units. SSL encodes a casein kinase 2 (CK2) β-subunit-like protein. Its putative ORF shares extensive (45%) homology with the genuine β-subunit of CK2 and retains the conserved C-terminal and Glu/Asp-rich domains that are essential for CK2 holoenzyme regulation. SSL maps within region 60D1–2 of D. melanogaster and D. simulans polytene chromosomes. We present evidence that SSL was derived from the genuine βCK2 gene by reverse transcription. This event resulted in the loss of the first three introns in the coding region of the SSL ancestor gene. Evolutionary analysis indicates that SSL has evolved under selective pressure at the translational level. Its sequence, especially in the 3′ region, is much closer to the Y-linked Su(Ste) tandem repeats than to the βCK2 gene. These results suggest that the acquisition of testis-specific autosomal genes may be important for the evolution of Drosophila as well as human Y chromosomes.